Roboticists' Imaginaries of Robots for Care: The Radical Imaginary as a Tool for an Ethical Discussion. Issue 3 (1st September 2020) - Vallès-Peris, Núria; Domènech, Miquel
Abstract : In this paper we analyze imaginaries about care robots using a set of interviews with roboticists. The study of imaginaries – from a notion close to that of Castoriadis's radical imaginary – is used as a tool to unravel ethical, political and social concerns that care robots entail. From the analysis of the interviews, our results highlight that imaginaries regarding care robots are predominantly sustained by a social process of care fragmentation. The translation of the imaginary of industry robots into the wildness of the daily life in healthcare reconfigures the comprehension of robots and their mediations. This process is intensively linked to Human Robot Collaboration (HRC) and Artificial Intelligence (AI) imaginaries of care, based on the cult of domesticity and the opposition of human caring to rational caring. We see how these fragmentations are in tension with an approach that seeks to integrate the ethics of care with technoscience, which has relevant consequences for the ethical debate on care robotics and the political significance of care in our world.